Genome-wide binding and mechanistic analyses of Smchd1-mediated epigenetic regulation - Chen, Kelan (Proc Natl Acad Sci U S A, 2015)
Structural maintenance of chromosomes flexible hinge domain containing 1 (Smchd1) is an epigenetic repressor with described roles in X inactivation and genomic imprinting, but Smchd1 is also critically involved in the pathogenesis of facioscapulohumeral dystrophy. The underlying molecular mechanism by which Smchd1 functions in these instances remains unknown. Our genome-wide transcriptional and epigenetic analyses show that Smchd1 binds cis-regulatory elements, many of which coincide with CCCTC-binding factor (Ctcf) binding sites, for example, the clustered protocadherin (Pcdh) genes, where we show Smchd1 and Ctcf act in opposing ways. We provide biochemical and biophysical evidence that Smchd1–chromatin interactions are established through the homodimeric hinge domain of Smchd1 and, intriguingly, that the hinge domain also has the capacity to bind DNA and RNA. Our results suggest Smchd1 imparts epigenetic regulation via physical association with chromatin, which may antagonize Ctcf-facilitated chromatin interactions, resulting in coordinated transcriptional control.